Removal of ciprofloxacin from aqueous solution by rabbit manure biochar - Huang, Wen (Environmental technology, 2020)
Biochar was prepared from rabbit faeces at 400°C, 500°C, 600°C, and 700°C, respectively (labelled RFB400, RFB500, RFB600, and RFB700, respectively), and was characterized by elemental analysis, BET, SEM and FTIR. The adsorption factors, kinetics, isothermal adsorption and thermodynamics of the adsorption properties were investigated in batch experiments. The results showed that RFB possessed a large specific surface area and was rich in pore structure, and the aromaticity and stability increased with the pyrolysis temperature of the biochar. When the solution pH was 11, adsorption achieved equilibrium at approximately 180 min. The kinetic data were well-represented by the pseudo-second-order model, indicating that the adsorption rate was jointly controlled by liquid film diffusion, surface adsorption and intra-particle diffusion. The results of isothermal adsorption and thermodynamics showed that the adsorption behaviour of CIP (ciprofloxacin) onto RFB was better fitted with the Langmuir model, and the adsorption process was spontaneous and endothermic. FTIR studies showed that RFB was rich in oxygen-containing functional groups and that hydrogen bonds and π-π bonds were closely related to the adsorption process. This work showed that the rabbit faeces-derived biochar has promise as an effective adsorbent to remove ciprofloxacin from wastewater